CLASSIFICATION OF MEDICINAL PROPERTIES OF ACHILLEA MILLEFOLIUM ACCORDING TO BIOCHEMICAL PROPERTIES (Ustozlar uchun, 2025)
Achillea millefolium plant species, distribution, medical importance, role in modern medicine, chemical composition, organic and inorganic substances, medicinal properties, physiological and morphological changes are covered.